Factors Related to Responsiveness of Local Health Security Committee to Local Health Security Fund in Pathumthani Province - เหมือนโพธิ์ทอง สัญญา; ตรีเดช ปิยธิดา; ปั้นดี วงเดือน (Journal of Preventive Medicine Association of Thailand, 2018)
This study was a survey research. The objectives were to assess the level of responsiveness of Local Health Security Committee (LHSC) to Local Health Security Fund (LHSF), and to explore the associated factors. The sample consisted of 193 members of the LHSC of Pathumthani province. Statistical analysis included mean, standard deviation, Chi-square, and Pearson’s product moment correlation coefficient. The study found that the overall responsiveness of LHSC was high level with mean =2.53, standard deviation =0.39. Association of knowledge about LHSF, perception about the benefit of LHSF and perception about the rule of the LHSF committee with the responsiveness to LHSF had statistical significance were 0.354, 0.748, and 0.770 (p<.001) consecutively. Furthermore, the motivation factor on the receiving of information and news about LHSF statistical significant was associated with responsiveness (p<.001) Therefore, perception about the role, function and benefit of LHSF knowledge and information relating to LHSF should be promoted and supported in order to increase the efficiency of the performance of the LHSC Committee. Health manpower development plan of LHSF should bemore focused than before.